The WEFE nexus and the climate crisis: Major challenges, great opportunities - Immerzeel, Walter; Gyawali, Dipak; Khalid, Sidra (CGIAR, 2024)
This webinar discusses the complex relationships between water, energy, food, and ecosystems (WEFE) in the context of the climate crisis. It explores the interconnectedness of these vital elements and their responses to the urgent challenges posed by the changing climate.